Effect of models project based learning and metacognitive skills in improving undergraduate students’ creative thinking abilities - Sene, Mikael; Riyanto, Yatim; Bachri, Bachtiar Syaiful (Edelweiss Applied Science and Technology, 2025)
This study examines the effect of Project-Based Learning (PjBL) and metacognitive skills on undergraduate students’ creative thinking ability (CTA). The method used is a factorial experimental design with a pre-test post-test control group model. The sample consisted of 120 students at Weetebula Catholic University. The research instruments were a questionnaire to measure metacognitive skills and a test to measure CTA. Data analysis was carried out using ANOVA and MANOVA to test the influence of variables. The results showed: (1) the experimental group had a higher average CTA (80.30) than the control group (64.30); (2) the PjBL model had a significant effect on students’ CTA (p < 0.05); (3) metacognitive skills also had a significant effect on CTA (p < 0.05); and (4) there is a simultaneous influence of the PjBL model and metacognitive skills on CTA (p < 0.05). These findings recommend the application of the PjBL model combined with strengthening metacognitive skills as an effective strategy to improve the CTA of undergraduate students. Practically, the results of this study can serve as a reference for lecturers and educational institutions to develop more innovative learning methods and support the development of students’ CTA in the context of higher learning.